Long-Term Effects of Individual-Focused and Team-Based Training on Health Professionals' Intention to Have Serious Illness Conversations: A Cluster Randomised Trial - Dalil Asmaou Bouba; Lucas Gomes Souza; Suélène Georgina Dofara; Sabrina Guay-Bélanger; Souleymane Gadio; Diogo Mochcovitch; Jean-Sébastien Paquette; Shigeko (Seiko); Patrick Archambault; Annette M. Totten; Louis-Paul Rivest; France Légaré (Taylor & Francis Group, 2024)
We aimed to measure the sustainability of health professionals' intention to have serious illness conversations with patients using the Serious Illness Conversation Guide (SICG) after individual-focused training versus team-based training. In a cluster randomised trial, we trained healthcare professionals in 40 primary care clinics and measured their intention to hold serious illness conversations immediately (T1), after 1 year (T2) and after 2 years (T3). Primary care clinics (n = 40) were randomly assigned to individual-focused training (comparator) or team-based training (intervention). Average age of the 373 participants was 35-44 years, 79% were women. On a scale of 1 to 7, at T1, the mean intention was 5.33 (SD 0.20) in the individual-focused group and 5.36 (SD 0.18) in the team-based group; at T2, these scores were 4.94 (SD 0.23) and 4.87 (SD 0.21) and at T3, 5.14 (SD 0.24) and 4.59 (SD 0.21), respectively. At T3, the difference in mean intention between study groups had a significant p-value of 0.01. Intention to have serious illness conversations was lower at T2 and T3 after team-based training than after individual-focused training, with a significant difference at 2 years in favour of individual-focused training. Health professionals reported not enough time during consultations for serious illness conversations as a major barrier.Registration number: ClinicalTrials.gov (ID NCT03577002) for the parent clinical trial.